Improved pollination efficiency and reduced honey bee colony decline in greenhouses by allowing access to the outside during part of the day - Nicodemo, D. [UNESP]; Malheiros, E. B. [UNESP]; De Jong, D.; Couto, R. H.N. [UNESP] (Universidade Estadual de Feira de Santana, 2018)
Although honey bees are efficient pollinators of many crops cultivated in greenhouses, it is difficult to maintain colony strength and consequently pollination efficiency. Many bees die under greenhouse conditions and the colonies rapidly weaken. We examined the effect of adaptations to the hive entrance that allowed control of whether and when bees had access to the outside environment to see how it would affect pollination efficiency and colony condition in greenhouses with flowering cucumber (Cucumis sativus) plants in comparison with colonies that remained constantly inside the greenhouse. We recorded the type and period of visitation to the cucumber flowers, numbers of honey bees entering and leaving the two-entrance hives and the effect of this type of management on the quantity of brood and food. Five frame Langstroth “nucleus” colonies were equipped with two 30 square centimeter entrances and two 3.0 cm diameter circular openings. Allowing the bees to make visits outside the greenhouse in early morning with redirection of bees into the greenhouse at 8:30 a.m. did not reduce visitation to cucumber flowers in the greenhouse. Maintaining colonies in the greenhouse reduced brood area and food stores. These losses were significantly reduced in colonies that had access to the outside during the early morning. Another advantage of alternating access to the inside and the outside of the greenhouse was that there was less possibility of interactions between bees and people working on the crop; also, pesticide applications could be made without directly affecting foraging bees.
Keywords: Apis mellifera; Brood; Cucumber; Cucumis sativus; Fruit set; Honey.